FOUNDATIONS FOR STRUCTURAL UNSTABLE SOILS - Natalia Yurievna Botvineva; Irina Sergeevna Burakova; Olga Grigoryevna Fomenko (Современная наука и инновации)
The paper studied the effect of stress effects on permafrost in the construction of buildings and structures. A review of existing methods of conservation status ofpermafrost grounds. To study the compressibility offrozen soils odometers are used for thawing with heating equipment. The sample is placed in the device, given vertical load. Calculations and experience show that solid foundations and foundation-walls are notprofitable. Currently, developed spatial construction of foundations.